Prospects for Phagоtherapy of Bacterial Infections Associated with the Provision of Medical Care - A. D. Daudova; R. O. Abdrakhmanova; A. L. Yasenyavskaya; Ju. Z. Demina; M. O. Rubalsky; O. V. Rubalsky; M. A. Samotrueva; O. A. Bashkina (Антибиотики и Химиотерапия)
Healthcare-associated infections (HAIs) are a global medical and socioeconomic problem. Nosocomial infections occupy one of the leading places among the causes of death in the Russian Federation. About 60–70% of all nosocomial infections are associated with the use of medical implants of various proﬁles. Pseudomonas aeruginosa, various types of streptococci, staphylococci, Escherichia coli, enterococci (Enterococcus faecalis), Klebsiella pneumoniae, Proteus mirabilis, and representatives of the genus Acinetobacter are highly  likely to be found  in bioﬁlms of medical supplies. A distinctive feature of microbes that cause  HAIs is poly- or even  pan-resistance of microbes to recommended antimicrobials. The search  for methods and means to overcome is a priority task of modern medicine. Phage therapy seems to be one of the logical and promising ways to combat bacteria that are resistant to conventional therapy. The article outlines the advantages and disadvantages of phage therapy, provides an overview of the successful use of mono- and combined preparations of bacteriophages in the experiment and clinic, as well as modern directions for the use of bacteriophages not only for therapeutic, but also for prophylactic purposes, based on the latest achievements of genetic engineering and biotechnology.